Antimicrobial effects of the macrocyclic Cu(II)-tetraanhydroaminobenzaldehyde complex - Jantová, S; Labuda, J; Vollek, V; Zastková, M (Folia microbiologica, 1997)
The Cu(II)-tetraaza macrocyclic complex exhibited antimicrobial effects on bacteria, yeasts and filamentous fungi. The highest antibacterial activity was found with B. subtilis and S. aureus, the respective IC50 values being 18 and 80 micrograms/L and the MIC values 50 and 1000 micrograms/L. A concentration of 1 mg/L exerted a bacteriocide effect on S. aureus. The MIC value for B. subtilis was 250 times lower and for P. aeruginosa 10 times lower than the corresponding values for ampicillin. The Cu-complex was inactive against all tested yeasts. The strongest antifungal effect was manifested for R. nigricans, with an IC50 value under 0.1 mg/L, whereas in A. alternata the IC50 was 13.5 mg/L.
Keywords: antibakteriální látky; Microbial Sensitivity Tests; Organometallic Compounds; Bacillus subtilis; Escherichia coli; mikrobiální testy citlivosti; antifungální látky; Antifungal Agents; Superoxide Dismutase; superoxiddismutasa; organokovové sloučeniny; Staphylococcus aureus; Pseudomonas aeruginosa; Anti-Bacterial Agents